Strategies for Managing Perfluorinated Compounds (PFCs) in Semiconductor Manufacturing: A Supply Chain and Public Management Approach - Luo, Ziqiao; Gu, Mingyan; Quan, Quan; Jiang, Zizhan; Wang, ChengMing (Transactions on Engineering and Technology Research, 2024)
The semiconductor industry stands as a pillar of modern technological progression, yet it grapples with significant environmental challenges, predominantly due to the emissions of perfluorinated compounds (PFCs). PFCs, critical in semiconductor manufacturing processes like dry etching and chemical vapor deposition (CVD) chamber cleaning, present a dire environmental concern given their high Global Warming Potential (GWP) and persistent nature. This treatise delves into a comprehensive analysis of how supply chain management and astute public policy can mitigate the deleterious impact of PFCs. It methodically scrutinizes the current challenges in curbing these emissions, assesses the efficacy of prevailing strategies, and champions the inception of trailblazing abatement technologies alongside forward-thinking regulatory frameworks. The research presents a critical evaluation of the interplay between stringent environmental requirements and the semiconductor industry's economic and innovation imperatives. It underscores the intricacies of aligning the sector's operations with sustainable practices while maintaining its economic vitality and capacity for innovation. Through a meticulous exploration of advanced material alternatives, state-of-the-art emissions control technologies, and progressive policy initiatives, this paper endeavors to steer the semiconductor industry towards a future where environmental sustainability becomes a cornerstone of its developmental ethos without stifling its technological evolution or economic robustness.